The oxidant-antioxidant imbalance was involved in the pathogenesis of chronic rhinosinusitis with nasal polyps - Zhou, Jing; Zhou, Jiao; Liu, Ruowu; Liu, Yafeng; Meng, Juan; Wen, Qiao; Luo, Yirui; Liu, Shixi; Li, Huabin; Ba, Luo; Du, Jintao (Frontiers in Immunology, 2024)
Background: Although Ooxidative stress is involved in the pathophysiological process of chronic rhinosinusitis with nasal polyps (CRSwNP), but the specific underlying mechanism is still unclear. Whether antioxidant therapy can treat CRSwNP needs further investigation.Methods: Immunohistochemistry, immunofluorescence, western blotting and quantitative polymerase chain reaction (qPCR) analyses were performed to detect the distribution and expression of oxidants and antioxidants in nasal polyp tissues. qPCR revealed correlations Correlation was examined with qPCR between oxidase, antioxidant enzymesantioxidase and inflammatory cytokine levelscytokines in CRSwNP patients. Human nasal epithelial cells (HNEpCs) and primary macrophages were cultured to track the cellular origin of oxidative stress in nasal polyps(NPs) and to determineestimate whether crocin can reduce cellular inflammation by increasing the cellularenhancing antioxidant capacity.The expression of NOS2, NOX1, HO-1 and SOD2 increased and was increasedenriched in nasal epithelial cells and macrophages derived of from nasal polyps tissue. Oxidase levels were positively correlated with those of inflammatory cytokines (IL-5 and IL-6). Conversely, the levels of antioxidant enzymes were negatively correlated with those of IL-13 and IFN-γ. Crocin could inhibited M1 and M2 macrophage polarization as well as the expression of NOS2 and NOX1, and improved the antioxidant capacity in M2 polarizationof M2 macrophages. Moreover, crocin enhanced the antioxidant ability of antioxidants to reduce inflammation via the KEAP1/NRF2/HO-1 pathway in HNEpCs treated with SEB or LPS. Additionally, we observed the antioxidant and anti-inflammatory effects of crocin in nasal explants.Oxidative stress plays an important role in the development of CRSwNP by promoting various types of inflammation. The oxidative stress of nasal polyps comes from epithelial cells and macrophages. Crocin can inhibit Inhibition of oxidative reactions by crocin couldand reduce inflammation via the KEAP1/NRF2/HO-1 pathway. Antioxidant therapy may be a promising strategy for treating CRSwNP.